1991
DOI: 10.1111/j.1600-9657.1991.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Canal markings produced by endosonic instruments

Abstract: It has been recognised that ultrasonic files leave a diagonal pattern within the canal following endosonic instrumentation. There is confusion on the causative factor on the production of these marks. Furthermore there is little information about the marks produced by sonic files. An in vitro system consisting of highly polished dentin discs demonstrated that the ultrasonic K-file made a diagonal pattern that was an imprint of the cutting edges of the file. The sonic files produced different markings which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…In addition, it is difficult to control the cutting of dentin during UI and hence the shape of the prepared root canal. Strip perforations as well as highly irregular-shaped canals were frequently produced (128,146). Therefore, UI is not generally perceived as an alternative to conventional hand instrumentation (101,125,139,147).…”
Section: Ultrasonicsmentioning
confidence: 98%
“…In addition, it is difficult to control the cutting of dentin during UI and hence the shape of the prepared root canal. Strip perforations as well as highly irregular-shaped canals were frequently produced (128,146). Therefore, UI is not generally perceived as an alternative to conventional hand instrumentation (101,125,139,147).…”
Section: Ultrasonicsmentioning
confidence: 98%
“…A freely oscillating instrument will cause more ultrasound effects in the irrigating solution than a file that binds in the root canal. 125 Furthermore, use of ultrasonic files during canal preparation may lead to gouging of the root canal walls 126 and severe transportation of the canal with zipping and strip perforations. 127 Several clinical studies have reported greater canal and isthmus cleanliness in the apical region of the root canal when passive ultrasonic activation has been used following canal preparation.…”
Section: Use Of Ultrasonics To Enhance Root Canal Cleaningmentioning
confidence: 99%
“…Because agitation of irrigants has been shown to increase irrigation effectiveness (13), various manual agitation techniques and machine-assisted agitation devices have been developed (14). Continuous ultrasonic irrigation has been shown to produce cleaner canals and isthmuses (15)(16)(17); however, ultrasonic irrigation must be used with care because procedural accidents (canal transportation, zipping, perforation) and creating an irregularly shaped canal preparation are possible, especially in curved canals (18)(19)(20). Another aspect of irrigation effectiveness is volume.…”
mentioning
confidence: 99%